Using an active Radio Frequency Identification Real-Time Location System to remotely monitor animal movement in zoos. Issue 1 (December 2016) - Scott, Nancy; Hansen, Bernard; LaDue, Chase; Lam, Carlson; Lai, Albert; Chan, Lowell
Abstract Background Radio and satellite telemetry collars have been used across taxa, including with elephants, in situ for decades to collect data used for various analyses. To quantify the movement patterns of African elephants, Loxodonta africana, in a zoo, we modified a Real-Time Location System using active Radio Frequency Identification tags originally developed for inventory and asset tracking in warehouses. This is the first phase of a multi-phase project that we have termed the Real-Time Observer of Animal Movement. It allows for the continuous data collection and data analytics of elephant movement and space use in a mixed-species African savanna habitat at the Dallas Zoo. This system could prove to be a useful remote welfare tool for a variety of animal species at multiple facilities. Results We determined that a Real-Time Location System using Radio Frequency Identification tags could be used to continuously monitor elephant movement, social relationships, and exhibit use remotely over several acres in a zoo with a volume of data not otherwise possible to achieve. Real-time visual outputs include current location in the habitat, paths taken around the habitat, habitat preferences, social relationships between the elephants, and data tables with average rate of travel and distance traveled. Conclusions The pilot system at the Dallas Zoo is the first-ever use of active Radio Frequency Identification technology to observe zoo animal behavior patterns and monitor welfare. It has proven to be an effective tool for efficiently collecting data continuously and remotely throughout the day and night. It represents the first phase of a multifaceted project that will add capabilities and functionality for additional species and other zoos to form a network for sharing data to inform captive animal management strategies.